Pengaruh Teknik Permainan Menyusun Kata Terhadap Kemampuan Membaca Permulaan Pada Mata Pelajaran Bahasa Indonesia Siswa Kelas I UPTD SD Negeri 18 Mendobarat - Siski Marsanda; Romadon; Silvio Juliana Nabela (JBES (Journal Basic Education Skills), 2025)
This study is motivated by the low early reading skills of first-grade students at UPTD SD Negeri 18 Mendobarat, particularly in recognizing letters, forming syllables, and constructing words. The purpose of this study is to determine the effect of the Word Construction Game Technique on early reading skills in the Indonesian Language subject among first-grade students at UPTD SD Negeri 18 Mendobarat. The research method used is an experimental "Quasi-Experiment" (Nonequivalent Control Group Design). The sample in this study was selected using purposive sampling. The sample consists of first-grade students from SD Negeri 18 Mendobarat, with Class I A, totaling 28 students, serving as the control group, and Class I B, totaling 28 students, serving as the experimental group. Data analysis techniques used in this study include normality testing, homogeneity testing, and hypothesis testing using paired t-test. The pretest results showed that there was no significant difference between the control and experimental groups (tcount = 1.876; ttable = 2.003; H0 was accepted and Ha was rejected). However, the posttest results showed that there were significant differences after treatment (tcount = 2.875; ttable = 2.003; H0 was rejected and Ha was accepted). In conclusion, the word composing game technique has a positive effect on students' initial reading abilities